Current status and prospects of research on the pollution and treatment technologies of per- and polyfluoroalkyl substances - Xuejiao Tang; He Yang; Xinya Li; Cuiping Wang (Desalination and Water Treatment)
Per- and polyfluoroalkyl substances (PFAS) are persistent organic pollutants characterized by high stability, durability, and biotoxicity. These properties pose significant risks to human health, driving researchers to seek more efficient PFAS degradation technologies. This article outlines the current contamination status of PFAS in environmental media and mainstream removal technologies. It innovatively analyzes PFAS pollution from multiple perspectives, including sources, environmental distribution, toxicological effects, and regional variations. Additionally, it provides a forward-looking perspective on future research directions, compares the principles, applications, efficiency, and cost-effectiveness of different technologies, and proposes a novel evaluation framework to guide technology selection and optimization. Compared to previous studies, this article offers a more comprehensive and systematic review of PFAS treatment technologies, aiming to serve as a valuable reference for developing advanced PFAS removal methods.